A C-type lectin from Crassostrea gigas with novel EFG/FVN motif involved in recognition of various PAMPs and induction of interleukin expression. (June 2023) - Ma, Youwen; Qiao, Xue; Dong, Miren; Lian, Xingye; Li, Yinan; Jin, Yuhao; Wang, Lingling; Song, Linsheng
Abstract: C-type lectins (CTLs) are a superfamily of Ca 2+ -dependent carbohydrate-recognition proteins, which participate in the nonself-recognition and triggering the transduction pathways in the innate immunity. In the present study, a novel CTL (designated as Cg CLEC-TM2) with a carbohydrate-recognition domain (CRD) and a transmembrane domain (TM) was identified from the Pacific oyster Crassostrea gigas . Two novel EFG and FVN motifs were found in Ca 2+ -binding site 2 of Cg CLEC-TM2. The mRNA transcripts of Cg CLEC-TM2 were detected in all tested tissues with the highest expression level in haemocytes, which was 94.41-fold ( p < 0.01) of that in adductor muscle. The relative expression level of Cg CLEC-TM2 in haemocytes significantly up-regulated at 6 h and 24 h after the stimulation of Vibrio splendidus, which was 4.94- and 12.77-fold of that in control group ( p < 0.01), respectively. The recombinant CRD of Cg CLEC-TM2 (rCRD) was able to bind lipopolysaccharide (LPS), mannose (MAN), peptidoglycan (PGN), and poly (I: C) in a Ca 2+ -dependent manner. The rCRD exhibited binding activity to V. anguillarum, Bacillus subtilis, V. splendidus, Escherichia coli, Pichia pastoris, Staphylococcus aureus and Micrococcus luteus in a Ca 2+ -dependent manner. The rCRD also exhibited agglutination activity to E. coli, V. splendidus, S. aureus, M. luteus and P. pastoris in a Ca 2+ -dependent manner. The phagocytosis rate of haemocytes towards V. splendidus significantly down-regulated from 27.2% to 20.9% after treatment of anti- Cg CLEC-TM2-CRD antibody, while the growth of V. splendidus and E. coli was inhibited compared with the TBS and rTrx groups. After the expression of Cg CLEC-TM2 was inhibited by RNAi, the expression level of phospho-extracellular regulated protein kinases (p- Cg ERK) in haemocytes, and the mRNA expressions of interleukin17s ( Cg IL17-1 and Cg IL17-4) decreased significantly after V. splendidus stimulation, compared with that in EGFP-RNAi oysters, respectively. These results suggested that Cg CLEC-TM2 with novel motifs served as a pattern recognition receptor (PRR) involved in the recognition of microorganisms, and induction of Cg IL17s expression in the immune response of oysters. Highlights: A single-CRD C-type lectin ( Cg CLEC-TM2) with novel FVN and EFG motif was identified from C. gigas. Cg CLEC-TM2 was able to recognize a variety of PAMPs and agglutinate microorganisms. Cg CLEC-TM2 improved the phagocytic ability of hemocytes and inhibited the growth of bacteria. Cg CLEC-TM2 induced the expression of Cg IL-17-1 and Cg IL-17-4 after Vibrio splendidus stimulation.